Nuevas localidades del zorrillo manchado del sur Spilogale angustifrons (Carnivora, Mephitidae) en Veracruz, México/ New locations of the Southern Spotted Skunk Spilogale angustifrons (Carnivora, Mephitidae) in Veracruz, Mexico - González Christen, Alvar; Guzmán Guzmán, Salvador; Alarcón Villegas, Luis E. (Instituto de Ecología, A.C., 2016)
We provide five new locations of the Southern Spotted Skunk Spilogale angustifrons Howell 1902 in Veracruz, Mexico. These records extend the known geographic distribution of this species in the Veracruz state.